(untitled) (Nexo Revista Científica, 2021)
The working hypothesis of the research is based on the assumption that the modernization of the organizational and economic mechanism for managing the innovative potential of an integrated agro-industrial formation allows the agroecosystem to adapt to the conditions of a competitive market environment as much as possible; modify applied technologies and develop new ones; build up innovative potential, which leads to an increase in the competitiveness of economic entities in the agro-industrial complex. On the basis of a systematic approach, the paper substantiates theoretical provisions and a set of recommendations for the formation of an organizational and economic mechanism for managing the innovative potential of integrated agro-industrial formations, in the development of which general scientific methods of analysis and synthesis were applied, as well as methods of scientific abstraction, functional and structural analysis, modeling method, theory and methodology of the systems approach and other methods of scientific knowledge. The paper substantiates the need for the formation of mechanisms tuned to maximize the implementation of the innovative potential of integrated agro-industrial formations, characterized by the predominance of the scientific and technological component with the inherent function of self-development and the ability to accelerate the development of the agro-industrial complex of meso-level economic systems. The organizational and economic mechanism for managing the innovative potential of integrated agro-industrial formations, presented as a system of tools and impact processes, can be applied in practice to obtain innovative results. The use of the proposed management tools will allow influencing innovative processes and ensuring the effectiveness of activities based on a synergistic effect. The scientific significance of the study lies in the development of theoretical and methodological provisions and scientific and practical recommendations aimed at forming an organizational and economic mechanism for managing the innovative potential of integrated agro-industrial formations.